Pemantauan Status Gizi Pada Remaja Yang Mengalami Dismenorea Di Kabupaten Bulukumba - Jusni Jusni; Kurniati Akhfar; Arfiani arfi (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2022)
Adolescence is a period of transition from childhood to adulthood which is characterized by accelerated physical, mental, emotional and social development. One of the changes that occur is menstruation. There are several factors that affect menstrual disorders, one of which is nutritional status. Many incidents of being overweight or underweight in young women have an impact on irregular menstrual cycles or can experience menstrual disorders, monitoring of the nutritional status of adolescents is necessary to prevent further nutritional problems in adulthood. This activity aims to monitor the nutritional status of adolescents with dysmenorrhea. This community service is carried out by monitoring nutritional status by measuring body weight, height, and the incidence of dysmenorrhea. The subjects of the service were all young women at the Tahirah Al Baeti Bulukumba Midwifery Academy as many as 46 respondents. The results of this activity were that 35% had an abnormal body mass index and 54% had dysmenorrhea. With this monitoring, it is hoped that the nutritional status of adolescents will become a concern and the incidence of dysmenorrhea can be controlled or decreased so that productive youth programs can be realized.